Perempuan dalam Media: Framing Berita Penyebaran Video Asusila Gisella Anastasia dan Michael Yakinobu Defretes - Siregar, Marakhilda; Ahmad, Entus Nuryana; Kusuma, Rr Chusnu Syarifa Diah (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The pornographic video case involving Indonesian public figures Gisella Anastasia and Michael Yakinobu De Fretes attracted widespread public attention in the end of 2020. Their legal status sparked debate, particularly regarding the application of Indonesia’s Pornography Law and questions of legal accountability. This study aims to analyze how two national media outlets, Tempo.co and Republika.co.id, framed their news coverage of the case. A qualitative descriptive approach was employed, utilizing Robert N. Entman’s framing analysis model, which consists of four key elements: defining problems, diagnosing causes, making moral judgments, and offering treatment recommendations. The research analyzed 16 online news articles published by the two media outlets during the peak of the controversy. The findings reveal that Tempo.co framed the incident as an act of criminalization against Gisella Anastasia, criticizing the legal action as disproportionate and suggesting a need for legal review. In contrast, Republika.co.id emphasized moral and personal aspects of Gisella’s identity, constructing a narrative that steered public opinion toward viewing her as culpable. Both media were also found to highlight sensational elements and economic interests in their reporting, while giving limited attention to the role of judicial institutions and the broader issue of legal justice. These findings suggest that media framing in this case not only reflects the ideological orientation of each outlet, but also serves as a tool for shaping public perception in alignment with particular interests.